Early life thermal stress: impacts on future temperature preference in weaned pigs (3 to 15 kg). (1st December 2020) - Robbins, Lindsey A; Green-Miller, Angela R; Johnson, Jay S; Gaskill, Brianna N
Abstract: Thermal stress can result in productivity losses, morbidity, and mortality if proper management practices are not employed. A basic understanding of the relationship between animals and the thermal environment is crucial to assess the environment's impact on livestock performance. Therefore, the study objective was to evaluate whether different early life thermal stressors (ELTS ) altered the temperature preference of pigs later in life. Twelve sows and their litters were randomly exposed to 1 of 3 ELTS treatments from 7 to 9 d of age: early life heat stress (ELHS ; cycling 32 to 38 °C; n = 4), early life cold stress (ELCS ; 25.4±1.1 °C without heating lamp; n = 4), or early life thermoneutral (ELTN ; 25.4±1.1 °C with a heating lamp; n = 4) conditions. From 10 to 20 d, (weaning) all piglets were exposed to ELTN conditions. At weaning, pigs were randomly assigned to groups of 4 of the same sex and ELTS treatment. Temperature preference, where pigs freely choose a temperature, was assessed in 21 groups ( n = 7 groups per ELTS treatment) using 1 of 3 thermal gradient apparatuses (22 to 40 °C). Testing began at 26 ± 1.3 d of age to give pigs time to acclimate to solid food after weaning and 1 group per ELTS treatment were tested simultaneously in each apparatus. Pigs were given 24 h to acclimate followed by a 24-h testing period. Behavior (active and inactive), posture (upright, sternal, and lateral lying), and location were documented every 20 min using instantaneous scan samples. Preferred feeding temperature was determined by the latency to empty a feeder in each location. Data were analyzed using PROC MIXED in SAS 9.4. A cubic regression model was used to calculate the peak temperature preference of pigs based on the temperature pigs spent most of their time. The preference range was calculated using peak temperature preference ±SE for each ELTS treatment group. Early life thermal stress altered where pigs spent most of their time within the thermal gradient ( P = 0.03) with ELTN pigs preferring cooler temperatures (peak preference of 23.8 °C) compared with their ELCS exposed counterparts (peak preference of 26.0 °C; P < 0.01). However, ELHS exposed pigs (peak preference of 25.6 °C) did not differ in their temperature preference compared with ELTN or ELCS exposed counterparts ( P > 0.05). In summary, ELCS exposure altered pig temperature preference later in life indicating that ELTS can alter temperature preference in pigs.